2019
DOI: 10.3928/00220124-20190516-09
|View full text |Cite
|
Sign up to set email alerts
|

Academic–Practice Partnerships: A Win-Win

Abstract: Partnerships between academia and practice can lead to improved patient care and health system innovations. Nurse educators in both academia and practice are positioned to facilitate opportunities for students and practicing nurses to be involved in evidence-based practice (EBP) care initiatives involving academic-health care partners in clinical and/or community-based systems. Best practices in collaborative partnerships have demonstrated the significance of their far-reaching impact on patients, students, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…It is the era for nurse educators to insist that academic systems secure research funding to support supercomputer technologies that can be used to analyze big data for predictive clinical models to yield health outcomes (WHO, 2020a). Nurse educators can also work to support academic-practice partnerships that foster workforce development opportunities, especially supporting overburdened health care workers (Phillips et al, 2019;Phillips et al, 2020).…”
Section: Message 4: Quality and Safety Education For Nurses Mastery Within Overwhelmed Health Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the era for nurse educators to insist that academic systems secure research funding to support supercomputer technologies that can be used to analyze big data for predictive clinical models to yield health outcomes (WHO, 2020a). Nurse educators can also work to support academic-practice partnerships that foster workforce development opportunities, especially supporting overburdened health care workers (Phillips et al, 2019;Phillips et al, 2020).…”
Section: Message 4: Quality and Safety Education For Nurses Mastery Within Overwhelmed Health Systemsmentioning
confidence: 99%
“…It is a process that connects the etiology of system-based problems to adverse consequences with improvement processes and outcomes (Notarnicola et al, 2019). An author-created model, the SAM (Phillips et al, 2016;Phillips et al, 2019) can be used by health care professionals as they navigate the challenges of the COVID-19 pandemic in health systems. Utilizing the SAM develops awareness of systems thinking, culminating in confidence and leadership in complex health systems.…”
mentioning
confidence: 99%
“…Students receive unique educational experiences to expand their understanding of the health care system, gain skills in managing chronic conditions, and improve their ability to translate EBP knowledge to population-focused environments (McClure et al, 2017). Students learn the application and necessity of implementing EBP as a part of daily patient care (Phillips et al, 2019). Moreover Breen et al (2019) found that students immersed in an APP experience developed an appreciation and respect for the contributions of peers and the work of school nurses in addressing asthma self-management for children.…”
Section: Liter Ature Re Vie Wmentioning
confidence: 99%
“…Phillips et al (2019) found that nurses who participated in an APP attended student EBP presentations, guided EBP care at the bedside, and learned how to search the literature for applicable evidence to improve clinical decision making, leading to the creation of sustainable EBP programs. Similarly, Glynn et al(2018), reported an increase in VA clinical faculty, educational programs, and Veterancentered publications following engagement in an APP.…”
mentioning
confidence: 99%
“…The AACN (2016AACN ( , 2021 has called for a paradigm shift in how academic and practice leaders work together. With different priorities, approaches, and baseline assumptions, it is important for both groups to identify common worldviews and develop a collaborative framework for addressing challenges, recognizing opportunities, and acting together to ensure the nation's nursing workforce is prepared to meet current and future demands within a transforming health care system (AACN, 2021;Beal & Zimmerman, 2019;Phillips et al, 2019;Sebastian et al, 2018). Examples of academic-practice partnerships are reported in the literature (AACN, 2016(AACN, , 2020, but there is limited evidence of partnerships seeking to understand differing perspectives, priorities, and challenges in order to collaborate in addressing nurse preparation for practice.…”
Section: Introductionmentioning
confidence: 99%